PERFORMANCE CONCRETE IN ROAD RIGID PAVEMENT MUARA PAHU – MOUNTAIN BAYAN IN THE DEPARTMENT OF PUBLIC WORKS DISTRICT WEST KUTAI - UDDIN, ASPAR (KURVA S JURNAL MAHASISWA, 2014)
Highway traffic is to serve both motor vehicles and non-motorized traffic with weights ranging from mild to severe, of course, this depends on the functional hierarchy of roads that are both outside and inside the city. Road maintenance concrete can be said to be zero even though its initial cost is higher than the asphalt road which always require regular maintenance, periodic maintenance, and upgrading of roads, it is appropriate if the concrete used on road sections were very busy as little as any road repairs done will invite congestion that would be a very broad impact.The purpose of the study is to examine the quality of the concrete results of the field work is in accordance with the mix design. While the aim to determine the quality of concrete were carried out in the field and to determine the implementation methods of casting, compaction, testing slump test, concrete for specimen retrieval and maintenance of the field test object.Results of research for the quality of cement concrete compressive strength characteristics of the field an average of thirty (30) samples f'cField= 247.687 Kg/cm2. Strength concrete compressive 85% of the characteristic (f'c x 0.85) = 210.534 Kg/cm2. Concrete compressive strength characteristics of an average of four (4) samples meet the required compressive strength characteristics of the plan are f'cField = 251.552 Kg/cm2 > f'cplant = 225,000 Kg/cm2. Concrete compressive strength characteristics of a standard deviation (f'c + 0.82 x S) = 250.559 Kg/cm2 > f'cPlant = 225,000 Kg/cm2.